HABITUS MEMBACA SISWA SMAN 2 DENPASAR - Fadhil, M Hasan; Arjawa, I Gusti Putu Bagus Suka; Kamajaya, Gede (Cahaya Ilmu Bangsa Institute, 2025)
This study aims to examine students' reading habits in schools using the concepts of agents, structures, capital, realms of practice, and efforts made by the school. Students' reading habits are influenced by interactions between agents, such as students, teachers, and parents, as well as social and cultural structures in the school environment. The social, cultural, and economic capital possessed by students plays an important role in shaping their reading habits. In addition, the realm of reading practices formed in schools, through literacy programs and facilities provided, also plays a role in influencing these habits. Thus, these factors are interrelated and shape the reading habitus that exists in students. In addition, this study is expected to provide deeper insight into the factors that shape students' reading habits. The role of efforts that can be made by schools in fostering positive reading habits among students. Schools have an important role in creating an environment that supports students' reading habits through various policies and initiatives. One effort that can be made by schools is to create a structure that supports reading habits through targeted policies, innovative reading programs, and the provision of adequate facilities. The results of this study are expected to not only provide a deeper understanding of how students' reading habits can be formed, but also provide practical suggestions for schools to improve students' reading habits. These steps are expected to help schools in creating a better literacy culture among students.